Effect of Superoxide Dismutase on Semen Parameters and Antioxidant Enzyme Activities of Liquid Stored (5°C) Mithun (Bos frontalis) Semen. (13th March 2014) - Perumal, P.
Abstract : The present study was undertaken to assess the effect of superoxide dismutase (SOD) on sperm motility, and viability; total sperm abnormality; acrosomal and plasma membrane integrity; DNA abnormality; antioxidant profiles such as catalase (CAT), reduced glutathione (GSH), and total antioxidant capacity (TAC); enzymatic profiles such as aspartate amino transaminase (AST), and alanine amino transaminase (ALT); and biochemical profiles such as malondialdehyde (MDA) production and cholesterol efflux. Total numbers of 50 ejaculates were collected twice a week from eight mithun bulls and semen was split into four equal aliquots, diluted with the TEYC extender. Group 1: semen without additives (control), and group 2 to group 4: semen was diluted with 50 U/mL, 100 U/mL, and 150 U/mL of SOD, respectively. These seminal parameters, antioxidant, enzymatic, and biochemical profiles were assessed at 5°C for 1, 6, 12, 24, and 30 h of incubation. Inclusion of SOD into diluent resulted in significant (P < 0.05 ) decrease in percentages of dead spermatozoa, abnormal spermatozoa, and acrosomal abnormalities at different hours of storage periods as compared with control group. Additionally, SOD at 100 U/mL has significant improvement in quality of mithun semen than SOD at 50 or 150 U/mL stored in in-vitro for up to 30 h. It was concluded that the possible protective effects of SOD on sperm parameters are that it prevents MDA production and preserves the antioxidants and intracellular enzymes during preservation.